Regional Climate Studies of China - Fu, Congbin; Jiang, Zhihong; Guan, Zhaoyong; He, Jinghai; Xu, Zhong-feng (Regional Climate Studies,, 2008)
Regional Climate of China is the first volume to present the latest research findings gained over the last decade which has greatly advanced our knowledge of the regional climate researches in China. A distinctive feature of the volume is that it is based on an integration of researches by using the advanced technologies, such as field observation and experiment, satellite information and numerical models in the regional climate studies.